Long-term effect of presurgical nasoalveolar molding on growth of maxillary arch in unilateral cleft lip and palate: randomized controlled trial. Issue 8 (August 2017) - Shetty, V.; Agrawal, R.K.; Sailer, H.F.
Abstract: The objective of this study was to investigate the long-term effect of presurgical nasoalveolar molding (PNAM) on growth of the maxillary arch through early childhood until 6 years of age in complete unilateral cleft lip and palate (UCLP) patients presenting for PNAM at different ages. Complete UCLP patients who were treated at our centre were divided into two groups. The study group underwent PNAM and was further subdivided into three subgroups (PNAM initiated within 1 month, between 1 and 6 months, and between 6 and 12 months of age in subgroup I, II, and III, respectively). The control group did not undergo PNAM and was further subdivided into three subgroups. Patients were evaluated at T1 (first visit), T2 (before cheiloplasty), and T3 (at 6 years). Between T1and T2, the intersegment distance (ISD) reduced significantly in the study group but increased in the control group, whereas the intercanine width (ICW) in both the study and control groups did not show significant change. Between T2 and T3, ISD and ICW were reduced significantly in the control group due to arch collapse, whereas in the study group, ISD reduced slightly with ICW remaining almost similar to noncleft norms. We conclude that reduced ISD following PNAM improves arch symmetry and stability, and thus may prevent arch collapse in the long term.